Textbook Development in Low Income Countries : A Guide for Policy and Practice - Crabbe, Richard A. B. (World Bank, Washington, DC, 2014)
Since 2003, over 220 million books have been distributed in primary schools in global partnership for education (GPE) countries. Despite this, a few years ago, a World Bank study highlighted the fact that there simply aren't enough textbooks for most students in Africa, and what is available is too expensive. The main objective of the this course is to equip anyone in a position to advise, administer, or design a book provision project with the necessary knowledge in order to make the appropriate input and right decisions. The focus throughout is on how to get affordable books to school children when and where needed. It is designed to be a practical resource that covers the key issues encountered in textbook provision, ranging from authorship through national publishing infrastructure to pricing, and distribution. The course is organized in 12 modules under four sections: understanding the textbook industry; book acquisition strategies; distribution strategies; and policy and practice. It provides functional knowledge of the workings of the book industry and its role in supporting learning and education. This will include detailed study of the work that publishers, printers, and distributors do. It also focuses on how the book industry costs books and the methods and trade-offs governments have to make in financing textbooks and supplementary readers.